THE ROLE OF SOCIAL MEDIA MARKETING AND CONSUMER EXPERIENCE AS A RESULT OF CUSTOMER BEHAVIOR - Fajarwati, Diana; Pratama, Achmad Difa; Fadli, Jul Aidil; Astuti, Puji (Jurnal Ilmu Manajemen (JIMMU), 2024)
This study highlights the important role of social media marketing activity (SMMA) and customer experience (CX) in shaping customer relationship quality on TikTok social media, with the aim of investigating the influence on customer relationship quality, and how this influence impacts purchase intention, loyalty intention, and participation intention. This study involved 504 respondents who were TikTok Shop users who had certain criteria using an online survey to measure six main variables through 47 statements. With this, the research developed a framework with the PLS-SEM method using SmartPLS. The results of this study show that all hypotheses are accepted and have a positive influence which indicates that consumer behavior, especially loyalty intention, has a high effect. good relationship quality increases loyalty intention because of trust, satisfaction, and transparent communication. SMMA and CX also play a role in influencing relationship quality by providing information and interactive content, and improving relationship quality. This research provides insight to companies regarding the potential of "TikTok" as a marketing channel to support sustainable business growth with marketing strategies that promote positive customer behavior by providing opportunities for marketers to develop strategies that focus more on visual creativity and marketing strategies through short videos, where Tiktok Shop can increase brand awareness and purchase intention can have a positive impact on marketing activities, increase brand awareness.